2008
DOI: 10.1055/s-0028-1085998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-thyroxine Replacement Therapy on Carotid Intima-media Thickness in Patients with Primary Hypothyroidism

Abstract: This report demonstrates that in patients with primary hypothyroidism, in addition to values of total cholesterol, LDL cholesterol, and total cholesterol/HDL cholesterol ratio, the CIMT value was higher compared to healthy controls. Importantly, the value of CIMT, as well as the levels of lipid parameters, decreased to normal level after L-thyroxine replacement therapy. Furthermore, significant correlations were detected between the changes of CIMT and the changes of total cholesterol and LDL cholesterol respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…We can therefore not completely exclude the possibility that the TBRs were higher during TSH suppression because the period of TSH suppression was longer. However, our findings seem to be in contrast to earlier studies showing a decrease in vascular disease with thyroid hormone replacement therapy in (subclinical) hypothyroidism [ 39 , 40 ]. This rather supports a detrimental effect of increased thyroid hormones on arterial inflammation.…”
Section: Discussioncontrasting
confidence: 99%
“…We can therefore not completely exclude the possibility that the TBRs were higher during TSH suppression because the period of TSH suppression was longer. However, our findings seem to be in contrast to earlier studies showing a decrease in vascular disease with thyroid hormone replacement therapy in (subclinical) hypothyroidism [ 39 , 40 ]. This rather supports a detrimental effect of increased thyroid hormones on arterial inflammation.…”
Section: Discussioncontrasting
confidence: 99%
“…Cakal et al have similarly established higher CAIMT in primary hypothyroid patients. 21,22 Their study has also found a positive correlation between lipids, CAIMT, and TSH levels and have concluded that CAIMT is an objective sign of accelerated atherosclerosis in patients with primary hypothyroidism. In contrast to these studies, Delitala et al in their study concluded that thyroid hormone was not associated with carotid artery plaque or increased CAIMT.…”
Section: Comparison Of Parameters After 4 Months Of Levothyroxine Amomentioning
confidence: 94%
“…Impaired intracellular glucose catabolism and GLUT4 translocation, decreased glycogen synthesis and glucose oxidation, and altered blood flow, have been proposed as underlying mechanisms [25, 26, 90, 93, 94]. Increased intima-media thickness of the common carotid artery has been reported in some studies in patients with overt hypothyroidism [53, 95, 96]. A higher frequency and/or severity of coronary heart disease [4, 97, 98] and an increased ischemic stroke risk [99] have been reported in patients with overt hypothyroidism.…”
Section: Thyroid Disease and Cardiovascular Riskmentioning
confidence: 99%